Assessment of color vision among health science students - Pandit, Rajan; Dhakal, R (Nepal Medical College Journal, 2020)
The synergistic and harmonic functions of retina, optic nerve, part of thalamus and visual cortex are essential for the perception of color: human color vision is trichromatic i.e. the mixture of red, green and blue lights. The present cross-sectional study was conducted in August to October 2018. The ethical approval was obtained from Institutional Review Committee (IRC) of Nepal Medical College. After obtaining consent from the participants, the study was carried out among health science students of age group 18-25 years at Jorpati, Kathmandu, Nepal. The number (n) of sample size was 300; (male, n=150, female, n=150). The assessment of color blindness was done with the help of Ishihara Chart (“Ishihara Type Tests for Color Blindness”-38 plates (2002) Eye Care- Ludhiana, India). Among the study group (male, n=150, female, n=150), the color deficiency were found in male participants only; n=7, which is 2.33% of total participants (n=300). None of the female participants were found to be color blind/weak. Among the color deficient (n=7), protanomaly detected in 1, deuteranomaly in 2 and deuteranopia in 4. Hence, the present students of health stream are future health workers, whose observation apt to clinical examination is instrumental to treat patients; therefore, they must be aware and circumspect of their color vision to discharge their duties to the patients in a better way.